The Role of Academics as Judges at the 8th UINSU Accounting Fair in Enhancing Students’ Accounting Competencies - Adi Harianto; Murdifin Azhar; Mhd Restu Razaq; Debora Tambunan; Roni Juliansyah; Sri Mauliza; Mega Sanjaya; Darwan Tanady; Martin; Ahmad Rivai (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This Community Service Program (PKM) aims to strengthen the accounting competencies of university students through the active involvement of academics as judges in Accounting Fair VIII at Universitas Islam Negeri Sumatera Utara (UINSU). The role of academics extends beyond evaluation, functioning as a medium for knowledge transfer, critical feedback, and competency benchmarking aligned with academic and industry standards. The program focuses on enhancing students’ understanding of accounting principles, analytical thinking, problem-solving skills, and professional judgment through competition-based activities such as quizzes, case studies, and financial analysis challenges. The implementation involves structured assessment by academic judges combined with direct feedback, enabling students to gain practical insights and improve readiness for real-world challenges. The results indicate a significant improvement in students’ competencies, particularly in analytical accuracy, confidence, and engagement in accounting learning. Thus, the involvement of academics as judges serves as a strategic approach to improving the quality of accounting education and preparing students for professional demands.